In vitro elution of amikacin, cefazolin, gentamicin, ampicillin/sulbactam, and meropenem from a commercially available calcium sulfate delivery kit - Maxwell, Elizabeth A.; Howell, Taylor; Mester, Rachel; Bennett, R. Avery; Cruz-Espindola, Crisanta; Boothe, Dawn (Frontiers in Veterinary Science, 2024)
To describe the elution kinetics of five antibiotics from a commercially available calcium sulfate local antibiotic delivery kit. A secondary goal was to compare elution concentrations with minimal inhibitory concentrations (MIC) for commonly encountered bacteria from the University of Florida's veterinary microbiology laboratory database. Calcium sulfate powder was combined with amikacin, cefazolin, gentamicin, ampicillin/sulbactam, and meropenem. Triplicates of antibiotic-loaded beads were immersed in 5 mL of phosphate-buffered saline (PBS) and kept at 37 degrees C under constant agitation. Antibiotic-conditioned PBS was sampled at 14 time points from 1-hour to 30 days and analyzed by liquid chromatography to determine the antibiotic concentration. All beads eluted concentrations of antibiotics for the 30day sampling period, except for ampicillin/sulbactam, with the most antibiotics being eluted within the first week. Mean observed peak concentrations occurred at 1-hour for all antibiotics, with a biphasic peak for all antibiotics, except ampicillin/sulbactam. The concentration of antibiotics within the eluent within the first 3 to 9 days (3-mm and 5-mm beads, respectively) was generally greater than the MIC of common isolates encountered by the UF Veterinary Diagnostic Lab. It was observed that the 5mm bead samples were superior in maintaining higher concentrations for a longer period, compared to the 3-mm beads. This information may be useful for clinical decision making for treatment of local infections encountered in practice.